2021
DOI: 10.15252/embj.2021109728
|View full text |Cite
|
Sign up to set email alerts
|

Helical ordering of envelope‐associated proteins and glycoproteins in respiratory syncytial virus

Abstract: Human respiratory syncytial virus (RSV) causes severe respiratory illness in children and the elderly. Here, using cryogenic electron microscopy and tomography combined with computational image analysis and three-dimensional reconstruction, we show that there is extensive helical ordering of the envelope-associated proteins and glycoproteins of RSV filamentous virions. We calculated a 16 A resolution sub-tomogram average of the matrix protein (M) layer that forms an endoskeleton below the viral envelope. These… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 75 publications
3
25
0
Order By: Relevance
“…Further characterisation of IBs morphogenesis in the presence of RSV helical NC should be of great interest, as the size and high flexibility of these structures could modulate IBs morphogenesis. A recent cryo-electron tomography study of RSV infected cells has revealed the presence of N rings in filamentous RSV particles (57), showing for the first time the heterogeneity of N assembly in the cell. The role of these structures during viral cycle i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Further characterisation of IBs morphogenesis in the presence of RSV helical NC should be of great interest, as the size and high flexibility of these structures could modulate IBs morphogenesis. A recent cryo-electron tomography study of RSV infected cells has revealed the presence of N rings in filamentous RSV particles (57), showing for the first time the heterogeneity of N assembly in the cell. The role of these structures during viral cycle i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Further characterisation of IBs morphogenesis in the presence of RSV helical NC should be of great interest, as the size and high flexibility of these structures could modulate IBs morphogenesis. Of note, a recent cryo-electron tomography study of RSV infected cells has revealed the presence of N rings in filamentous RSV particles (55), showing for the first time the heterogeneity of N assembly in the cell. The role of these structures during viral cycle i.e.…”
Section: Discussionmentioning
confidence: 98%
“…They also lacked the long-range helical ordering typical of RSV glycoproteins (Extended Data Fig. 3c,e) 23 . We designated these structures 'pseudotyped viruses' (Extended Data Fig.…”
Section: Articlementioning
confidence: 99%